2013
DOI: 10.1007/s12602-013-9145-z
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Antibacterial Mechanism of Action of Crude Garlic (Allium sativum) Clove Extract on Selected Probiotic Bifidobacterium Species as Revealed by SEM, TEM, and SDS-PAGE Analysis

Abstract: There has been much research on the effects of garlic (Allium sativum) on numerous pathogens, but very few, if any, studies on its effect on beneficial, probiotic bifidobacteria. We have recently shown that garlic exhibits antibacterial activity against bifidobacteria. The mechanism by which garlic kills bifidobacteria is yet to be elucidated. This study sought to determine the mechanism of action of garlic clove extract on selected Bifidobacterium species using scanning and transmission electron microscopy an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 23 publications
0
15
0
1
Order By: Relevance
“…Electron micrographs showed that garlic induced unusual morphological changes in bifidobacteria [5]. It is however not yet known whether garlic inhibition on probiotic cells is confined to the cell membrane or if there are other targets.…”
Section: Introductionmentioning
confidence: 99%
“…Electron micrographs showed that garlic induced unusual morphological changes in bifidobacteria [5]. It is however not yet known whether garlic inhibition on probiotic cells is confined to the cell membrane or if there are other targets.…”
Section: Introductionmentioning
confidence: 99%
“…Studies indicated that garlic could affect benefi cial probiotic Bifi dobacterium species in a manner similar to that exhibited in pathogens (Booyens et al 2014 ). The results highlight that caution should be taken especially when using raw garlic and probiotic bifi dobacteria simultaneously as the viability of these bacteria could be reduced by allicin released upon the crushing of garlic cloves, thereby limiting the health benefi ts that the consumer anticipates to gain from probiotics.…”
Section: +mentioning
confidence: 79%
“…Several mechanisms have been proposed for the antibiotic activity of garlic, including modulation of sulfhydryl enzymes, inhibition of RNA synthesis, and partial inhibition of DNA and protein synthesis [10]. Recently, Booyens et al (2014) investigated the antibacterial mechanism of crude garlic clove extract by using electron microscopy. The micrographs obtained showed the change of morphology such as cell elongation, distorted cells with bulbous ends and the condensation of cytoplasmic material, disintegration of membranes, loss of structural integrity of garlic clove extract-treated cells and leading to the cell death [11].…”
Section: Antibacterial Activities Of Garlic Extractmentioning
confidence: 99%
“…Recently, Booyens et al (2014) investigated the antibacterial mechanism of crude garlic clove extract by using electron microscopy. The micrographs obtained showed the change of morphology such as cell elongation, distorted cells with bulbous ends and the condensation of cytoplasmic material, disintegration of membranes, loss of structural integrity of garlic clove extract-treated cells and leading to the cell death [11].…”
Section: Antibacterial Activities Of Garlic Extractmentioning
confidence: 99%
See 1 more Smart Citation